The Role Of Using Educational Games And Social Interaction In Cultivating Students' Motivation To Learn Geometry - Arfatin Nurrahmah; Siti Khoirunnisa; Muhibatur Rohmatul Akhiroh; Fajar Sodik; Bunga Bunga (STABN RADEN WIJAYA WONOGIRI, 2023)
Learning mathematics, especially geometry material at the elementary school level, is often a challenge because students perceive this topic as abstract and less contextual, which has an impact on students' low learning motivation. This study aims to describe the application of educational game methods and the quality of social interaction on the formation of geometry learning motivation in grade 1 students of Tamansari 05 State Elementary School. This research uses a descriptive qualitative approach that focuses on an in-depth understanding of the situation in the field. Data were collected through participant observation, interviews with teachers and students, and documentation. The results showed a measurable positive impact, where active student participation increased from 38% to 88% after the implementation of educational games. This increase was also driven by more intensive social interactions, where 77% of students were recorded as actively discussing and helping each other solve challenges, compared to the previous learning which was only 42%. Overall, the average score of student learning motivation increased significantly from 57.69 ( low category) to 88.72 (very high category). This study concluded that the integration of educational game methods and strengthening social interactions is synergistically effective in increasing students' motivation to learn geometry